Peningkatan Literasi Perbankan Syariah Santri melalui Workshop Praktis Fiqh Muamalah di Pondok Pesantren Latansa Darussalam Palembang - Choiriyah Choiriyah; Dwi Noviani; Dwinda Fatimah Ishaq; Jordy Hairul Rafli (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
This community service activity aimed to improve students’ Islamic banking literacy through an experiential learning approach based on a fiqh muamalah workshop at Latansa Darussalam Islamic Boarding School, Palembang. The activity involved 100 participants consisting of students and teachers as an effort to strengthen understanding of Islamic economic and banking principles. The methods used in the activity included lectures, discussions, question-and-answer sessions, and simulations of sharia transaction practices, enabling participants not only to gain theoretical understanding but also practical experience in implementing sharia concepts. The evaluation was conducted using pre-test and post-test instruments in the form of multiple-choice questions and Likert scales to measure participants’ level of understanding before and after the activity. The evaluation results showed an increase in the participants’ average score from 55 to 82, with a gain score of 0.6, which falls into the moderate to high category. These findings indicate that an experience-based learning approach is effective in improving conceptual and practical understanding related to Islamic economics and is recommended for broader implementation in Islamic educational institutions.